Adding non-floral resources increases wild insect abundance but not yield in Australian hybrid carrot crops - Dawson, Blake M; Johnston, Nikolas P; Cerato, Stephanie; Rowbottom, Raylea; Spurr, Cameron; Davis, Abby; Rader, Romina (Basic and applied ecology, 2025)
Many insect pollinator-dependent crops heavily rely on managed honey bees for pollination, yet flies and other wild taxa can be highly abundant and efficient, thus having potential as complementary pollinators. However, unlike bees, fly pollinator life history requirements and foraging behaviour are often unsupported in agroecosystems, or completely unknown. We aimed to determine the effectiveness of different non-floral resources in attracting fly pollinators and supporting their life history requirements, and whether higher fly abundance would result in improved seed yield in hybrid carrot crops. We introduced three decomposing organic resources (carrion, manure, and carrot plant material) to four commercial carrot farms in Northern Tasmania, Australia and sampled fly activity on carrot umbels around each treatment. In total, we recorded 46 adult insect species visiting carrot umbels across all treatments, consisting of 32 Diptera (flies), eight Coleoptera (beetles), four Hymenoptera (bees, wasps and ants), and two Hemiptera (true bugs). We collected 10 fly species and one beetle species as larvae from the resources. Both the carrion and carrot treatments supported five different larval species, while the manure supported two. Only Lucilia sericata, Australophyra rostrata, and Oxysarcodexia varia were more abundant on carrot umbels around treatments compared to the control, and seed yield around the treatments did not differ to the control. Our results suggest that the inclusion of non-floral resources can fulfil the life history requirements of flies in agroecosystems. However, determining whether the addition of non-floral resources also results in increased yield, requires further investigation.